Effect of Tree Leaves and Malic Acid Supplementation to Wheat Straw Based Substrates on in Vitro Rumen Fermentation Parameters - Sarkar, Srobana; Mohini, Madhu; Nampoothiri, Vinu.M.; Mondal, Goutam; Pandita, Sujata (Indian Journal of Animal Nutrition, 2018)
This experiment was conducted to study the effects of addition of malic acid (MA) and tree leaves in straw based total mixed ration on in vitro rumen fermentation parameters. Four experimental substrates were prepared: Control (C-wheat straw and concentrate in 1: 1 ratio), T1 (45% wheat straw + 45% concentrate + 10% Leucaena leucocephala leaves), T2 (T1 diet + 1% MA), T3 (T1 diet + 2% MA). Inclusion of tree leaves increased(P